Investigation on Mechanical and Durability Properties of Rapid Strength Gaining Concrete - Krishnaraj, L; T. Ravichandran, P; AarifIlahi, Shaik; Ramanathan, V (International Journal of Engineering and Technology, 2018)
The strength of cement paste and aggregate components helps to decide the strength of the concrete, their properties of deformation, and the binding properties among the aggregate surface and cement paste. It is conceivable with many of the aggregates to form high strength concrete by increasing the cement paste strength, which can be controlled by choosing of water-content ratio and type of admixture dosage. The current scenario in the concrete technology and the accessibility of many kind of mineral and chemical admixtures, and special super plasticizer to gain the targeted compressive strength of a concrete. In this study MYK Remicrete PC30 and BASF Master Glennium ACE 30 were utilized as the admixtures as Add 1 and Add 2 which acts as high rate water reducing agents. These developments have led to increase uses of Rapid strength concrete. To compare the mechanical and durability properties of concrete using Fly ash and Admixtures the following tests were conducted on concrete tests specimens. Mechanical tests are to be conducted such as compressive strength tests, and tensile strength tests, durability tests like water absorption test, acid test by HCL, H2SO4 and HNO3. The result indicates that rate of development of compressive strength and tensile strength are higher for the concrete design mix which has HRWR admixture of 1% and FA of 20%.Â Â